Identification of Fire Ants (Hymenoptera: Formicidae) from Northeastern Mexico with Morphology and Molecular Markers - Sánchez Peña, Sergio R.; Chacón Cardosa, Manuela Citlali; Reséndez Pérez, Diana (2009)
RESUMEN La hormiga de fuego roja importada, Solenopsis invicta Buren, especie invasora, se ha dispersado exitosamente a muchos países desde su origen en Sudamérica, y ha alcanzado la frontera Estados Unidos-México (p. ej. Matamoros, estado de Tamaulipas, México) donde ahora coexiste con hormigas de fuego nativas, Solenopsis geminata y especies del subcomplejo Solenopsis xyloni. La identificación morfológica de las Solenopsis spp. es difícil, particularmente de las obreras más pequeñas. Examinamos la secuencia del gene mitocondrial citocromo oxidasa I (COI) como marcador para poblaciones de hormigas de fuego en varios sitios de México. Los productos de PCR de este locus rindieron secuencias únicas y patrones de restricción que permitieron distinguir entre S. invicta, S. geminata y caracterizar miembros del subcomplejo S. xyloni. Las secuencias de S. invicta fueron iguales en 99% a secuencias reportadas para especímenes de Florida y Nuevo México. Las secuencias de S. xyloni fueron iguales en 96% a las secuencias reportadas de Nuevo México. Las secuencias de S. geminata fueron similares (93% identidad) a las de Florida, y comparten un sitio de restricción Hinf I con algunas pero no todas las secuencias reportadas para Florida. Las secuencias de S. xyloni también se detectaron en hibridos de S. geminata/S. xyloni identificados por morfología; junto con otros caracteres el marcador permite su caracterización. ABSTRACT The invasive red imported fire ant, Solenopsis invicta Buren, has successfully dispersed across many countries from its South American homeland and now has reached the USMexico border (e.g., Matamoros, state of Tamaulipas, México), where it now coexists with native fire ants, Solenopsis geminata, Solenopsis xyloni, and others. The morphological identification of Solenopsis spp. workers is difficult, particularly small ones. We examined the sequence of the cytochrome oxidase I (COI) mitochondrial gene (mtDNA) as a marker for fire ants collected at several Mexican localities. PCR products from this locus yielded unique sequences and restriction patterns that allowed distinguishing between S. invicta, S. geminata, and specimens harboring S. xyloni sequences. The S. invicta sequences obtained were 99% identical to sequences reported from Florida and New Mexico specimens. The S. xyloni sequences obtained were 96% identical to New Mexico sequences. The S. geminata sequences were similar (93% identity) to those from Florida, and shared a Hinf I restriction site with some but not all Florida sequences. The S. xyloni sequences were detected in S. geminata/S. xyloni hybrids identified by morphology; along with other characters, the marker allows their characterization.